2020
DOI: 10.1155/2020/6658445
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Severity and Laboratory Parameters with Various Serotypes in Dengue Virus: A Hospital-Based Study

Abstract: Objectives. Dengue fever, being hyperendemic with analogous presentations as in many other acute febrile illnesses, poses a challenge in diagnosis during the acute stage. Additionally, the coexistence of multiple serotypes further complicates the disease prognosis. The study was undertaken to determine the dengue virus serotypes, clinical, and laboratory markers as predictors in the severity of infection. Methods. A prospective study was conducted among 106 patients admitted with acute febrile illness having p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 14 publications
(8 reference statements)
1
9
0
2
Order By: Relevance
“…The results obtained in the present study was in concordance to the previous report which was carried out using the clinical samples (106 patients) collected during the same period (2019) from Dakshina Kannada district of Karnataka. The study found that about 52.8% of cases were affected with DENV 3 serotype and the least common serotype found was DENV 1 (Rao et al, 2020). The important point to be noted is, all the serotypes existed during the study period, and DENV 3 is most prevalent in this geographical region.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…The results obtained in the present study was in concordance to the previous report which was carried out using the clinical samples (106 patients) collected during the same period (2019) from Dakshina Kannada district of Karnataka. The study found that about 52.8% of cases were affected with DENV 3 serotype and the least common serotype found was DENV 1 (Rao et al, 2020). The important point to be noted is, all the serotypes existed during the study period, and DENV 3 is most prevalent in this geographical region.…”
Section: Discussionmentioning
confidence: 83%
“…There are controversial reports regarding the association of DENV serotypes with the dengue severity. One study has reported the absence of link between dengue severity and serotypes (Rao et al, 2020). Few other studies argue that dengue severity is associated with DENV serotype (Vaughn et al, 2000;Kalayanarooj and Nimmannitya, 2000;Endy et al, 2002;Nisalak et al, 2003;Kumaria, 2010;Vicente et al, 2016;Rajesh et al, 2020;Gupta et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…https://www.nucleodoconhecimento.com.br RC: 102781 Disponível em: https://www.nucleodoconhecimento.com.br/saude/alteracoeshepaticas O fígado produz as enzimas AST e ALT que são consideradas marcadores de lesão hepática. Essas transaminases aumentam significativamente na infecção aguda da dengue e podem ser usadas como predição de gravidade da doença em casos agudos(RAO et al, 2020). correlacionando os resultados encontrados nos estudos com as alterações fisiológicas e laboratoriais de pacientes infectados por DENV.…”
unclassified
“…Essa informação corrobora com os resultados deWardhani et al (2017) que mostram os marcadores de gravidade mais frequentes em crianças do que em adultos. Alguns estudos observaram que as transaminases podem ser aliadas no prognóstico de uma hemorragia na infecção por dengue(RAO et al, 2020).https://www.nucleodoconhecimento.com.br RC: 102781 Disponível em: https://www.nucleodoconhecimento.com.br/saude/alteracoeshepaticas apresentaram aumento de 10 vezes nos pacientes que não sobreviveram em relação aos que sobreviveram. Assim como, os níveis de ALT apresentaram aumento também significativo para esse mesmo grupo, que não sobreviveram, mostrando que as alterações nos níveis plasmáticos dessas enzimas servem como marcadores de gravidade da doença.…”
unclassified